The Household Drinking Water Treatment Practices and Associated factors in the Case of Harar City, Eastern Ethiopia. - Worku, Ermias; Nigatu, Degu Bekele (Journal of Urban Development Studies, 2023)
Household water treatment containing boiling, chlorination, filtration and solar disinfection, can improve water quality at the point of use to prevent post-collection contamination. It is among the seven points of strategic areas announced by World Health Organization and United Nations Children’s Fund for prevention of diarrhea and other water borne diseases through community full participation. It is also a priority area of a current national drinking water quality monitoring strategic direction at country level which is implemented through the health extension program packages. This study assessed the households drinking water treatment practice and the factor that affect them in case of Harar Town; Eastern Ethiopia. A community based cross-sectional design was conducted in Harar town January-01-28, 2021. A total of 418 randomly selected households were involved in the study with response rate of 100%. Data were collected by using questionnaire and it was administer by face-to face interview. The data were analyzed using descriptive statistical tests and binary logistic regression. All independent variables with p- value of < 0.25 at bi-variate analysis were included in the multivariate model to determine the predictors of the outcome variable, and to control the confounding factors. For all statistical tests, a P value of ≤0.05 was a cut off point for statistically significant. The finding of the research indicates that level of household water treatment practice was 44.6%. Educational status of being literate (AOR = 1.877, 95 % CI = 0.71-5.015), pouring fetching water (AOR = 3.013, 95 % CI = 1.845-4.922), wash hands before collecting water (AOR = 1.833, 95 % CI = 1.1–3.052) and liquid waste disposal (AOR = 0.418, 95 % CI = 0.22-0.793) were significantly associated with household water treatment practice.